On the possible nature of deep magnetic sources of the Teisseyre-Thornquist Zone in connection with the heterogeneity of the lithosphere - Pashkevich, I.K.; Bakarzhieva, M.I. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2025)
A prerequisite for the formation of magnetic anomaly sources is the presence of crystal crustal stretching zones and increased mantle permeability. The highest concentration of sources is observed in the region bounded by meridional deep activation zones. It is characterised by increased permeability of the lithosphere, ‘blurring’ of the main geodynamic boundary and disruption of the structure of the transition layer under the Teisseyre-Thornquist zone (TTZ). The formation of magnetic sources under these favourable conditions is associated with lithospheric magmatism and fluidisation in the process of subduction. Its features are high-velocity southwest-dipping layers in the mantle to a depth of 500—600 km, identified as slabs, and ‘duplicate layers’ in the transition layer interpreted as ‘sunken’ slabs.